2018
DOI: 10.1111/ejss.12730
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanides in granulometric fractions of Mediterranean soils. Can they be used as fingerprints of provenance?

Abstract: There is geochemical interest in the lanthanides because they behave like a group that is closely related to the parent materials during surface processes, although they also undergo fractionation as a result of supergene dynamics. We analysed lanthanide concentrations (ICPms) in the granulometric fractions fine sand, clay and free forms of clay (FFclay‐CDB and FFclay‐Ox: extracted with citrate‐dithionite‐sodium bicarbonate and with ammonium oxalate, respectively) from a soil chronosequence of Mediterranean so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The chemical element composition (mean values per profile) of the whole fine sand (Tables 3 and 4) differed from that of the clay (Martín-García et al, 2019) in that the former contained lower quantities of major elements Al, Ca, Fe and K, and also lower quantities of most of the minor elements. This may be related, first, to the lower contents of phyllosilicates and, especially, of the (hydr)oxides goethite and haematite, in the fine sand, and, second, to the role of the clay fraction as a scavenger of heavy elements (Martín-García et al, 2016).…”
Section: Chemical Compositionmentioning
confidence: 92%
See 2 more Smart Citations
“…The chemical element composition (mean values per profile) of the whole fine sand (Tables 3 and 4) differed from that of the clay (Martín-García et al, 2019) in that the former contained lower quantities of major elements Al, Ca, Fe and K, and also lower quantities of most of the minor elements. This may be related, first, to the lower contents of phyllosilicates and, especially, of the (hydr)oxides goethite and haematite, in the fine sand, and, second, to the role of the clay fraction as a scavenger of heavy elements (Martín-García et al, 2016).…”
Section: Chemical Compositionmentioning
confidence: 92%
“…the existence of an authentic soil chronosequence, previously demonstrated by other compositional and morphological properties of the soils of the chronosequence (Calero et al, 2008(Calero et al, , 2009(Calero et al, , 2013Martín-García et al, 2016, 2019. No previous studies of chronofunctions established using the soil fine sand have been found in the bibliography.…”
Section: Soil Fine-sand Chronofunctionsmentioning
confidence: 96%
See 1 more Smart Citation